2000
DOI: 10.1530/eje.0.1420200
|View full text |Cite
|
Sign up to set email alerts
|

In the search for specific inhibitors of human 11beta-hydroxysteroid-dehydrogenases (11beta-HSDs): chenodeoxycholic acid selectively inhibits 11beta-HSD-I

Abstract: Objective: Selective inhibitors of 11b-hydroxysteroid-dehydrogenase type I may be of therapeutical interest for two reasons: i) 9a-Fluorinated 11-dehydrosteroids like 11-dehydro-dexamethasone (DH-D) are rapidly activated by human kidney 11b-hydroxysteroid-dehydrogenase type II (11b-HSD-II) to dexamethasone (D). If the same reaction by hepatic 11b-HSD-I could be selectively inhibited, DH-D could be used for selective renal immunosuppressive therapy. ii) Reduction of cortisone to cortisol in the liver may increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 46 publications
2
78
0
1
Order By: Relevance
“…There is controversy about the inhibitory effect of the bile acid CDCA on 11 -HSDs. Diederich et al (2000) suggested that CDCA acts as a selective 11 -HSD1 inhibitor, with an IC 50 of 2·8 µM obtained with human hepatic microsomes. Morris et al (2004) reported inhibition of the dehydrogenase activity of 11 -HSD1 with IC 50 values of 0·2-7 µM, but only 37-200 µM for the oxoreductase activity in rat liver microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy about the inhibitory effect of the bile acid CDCA on 11 -HSDs. Diederich et al (2000) suggested that CDCA acts as a selective 11 -HSD1 inhibitor, with an IC 50 of 2·8 µM obtained with human hepatic microsomes. Morris et al (2004) reported inhibition of the dehydrogenase activity of 11 -HSD1 with IC 50 values of 0·2-7 µM, but only 37-200 µM for the oxoreductase activity in rat liver microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…Activity Assays-Cleared lysates and other enzyme preparations (typically 1-10 l) were incubated in 0.5 ml of phosphate buffer (0.1 M, pH 7.6) containing 50,000 cpm [ 3 H]cortisol, 100 nM unlabeled cortisol, and 200 M NADP for 30 min at 37°C to assess dehydrogenase activity or [ 3 H]cortisone (generated as reported previously (19)), 100 nM unlabeled cortisone, 200 M NADPH, and a regeneration system (10 mM MgCl 2 , 5 mM glucose-6-phosphate, and 10 units glucose-6-phosphate dehydrogenase) (20) to assess reductase activity. Steroids were partitioned into 10 volumes of dichloromethane and separated by TLC using ethanol/chloroform (8:92) as the mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…The consequence is a conversion of an inactive 9-fluorinated 11-dehydrosteroid (e.g. 11-dehydrodexamethasone (11-DH-D)) to an active 11-hydroxysteroid (dexamethasone) in the kidney (51,56,122). These observations explain the greatly enhanced MC effect of 9a-fluorocortisol and the strong GC effect of dexamethasone.…”
Section: Synthetic Steroids and Their Metabolism By 11b-hsd-type2mentioning
confidence: 99%